Design of Narrowband and Wideband UHF Antennas for Partial Discharge Detection on High Voltage Equipment - Peerawut Yutthagowith; Thanatorn Mai-Eiam; P. Nimsanong (My University, 2024)
This paper presents designs for ultra-high-frequency (UHF) electromagnetic sensors based on printed circuit board (PCB) antennas for partial discharge (PD) detection in gas-insulated substations (GIS) applications. The sensors were designed to meet the requirement of narrowband/wideband UHF measuring systems for the UHF PD detection in GIS. The PD signals in the physical characteristic of the high-frequency electromagnetic (EM) wave were detected using the designed UHF antennas, which include the inset-fed rectangular microstrip patch (IFRMP) antennas, known for their narrowband characteristics that offer high interference signal rejection to improve signal-to-noise ratio and the two arm Archimedean spiral (TAAS) antennas, recognized for their broadband frequency spectrum capability. Because UHF PD signals are typically detected using various field sensor designs, both IFRMP and TAAS antennas were designed for three different models under calculation and simulation using MATLAB to apply in different operating frequency bands within the UHF range of PD detection (300 MHz-3 GHz). The designed UHF antennas have very characteristics, i.e. portable, lightweight, and attractive for practical applications with a low fabrication cost. Additionally, they are more convenient to install on the insulating flange compared to some types of external antenna sensors. In terms of antenna performance, they exhibit parameters like return loss (parameter S11) less than -10 dB and voltage standing wave ratio (VSWR) less than 2 within a close range of the designed operating frequency. Using the designed antennas, the phase-resolved PD (PRPD) patterns, the statistical magnitudes and waveforms of detected UHF signal have been obtained from laboratory testing for the sensitivity verification to help users in the effective application of the UHF PD detection.
Keywords: High voltage insulation and dielectric phenomena; Thermal Analysis in Power Transmission; Advanced Fiber Optic Sensors